FEM for improvement of damage prediction of airfield flexible pavements on soft and stiff subgrade under various heavy load configurations of landing gear of new generation aircraft - Ambassa Zoa; Cyprien Felix Ossende Owona (Curved and Layered Structures)
This study establishes the state-of-the-art requirements verification process applied to compute the damage of flexible airfield pavement from new French rational method. Flexible pavement structures with platforms A, B, C, and D, recommended by International Civil Aviation Organization (ICAO), were modelled under static loading of bogies from heavy weight aircrafts A340, B777, and A380 using Cast3M 3D finite element modelling. From the results of these computations, it appears that these structures A, B, C, and D recommended by ICAO are not equivalent from the point of view of mechanical behaviour as claimed by the empirical method for the design of aeronautical bituminous pavements with abacus. The representation of the strain shapes was done with 3D and 2D profiles to improve the quality of response and to clearly identify the critical areas when an aircraft bogie is passing. The four- and six-wheels bogies of the aircraft A380 are more destructive to flexible pavements than the bogies of the other aircrafts tested in this study. The calculation of damage according to the new French rational method for aeronautical flexible pavements revealed that the main damage to these pavements is due to the fatigue of the bituminous layers and not the rutting of subgrade and the unbound granular material layers.